Comparative perspectives on social movements political opportunities, mobilizing structures, and cultural framings - McAdam, Doug 1951-; McCarthy, John D. 1940-; Zald, Mayer N. 1931- (Cambridge studies in comparative politics, 1996)
Social movements such as environmentalism, feminism, nationalism, and the anti-immigration movement are a prominent feature of the modern world and have attracted increasing attention from scholars in many countries. Comparative Perspectives on Social Movements, first published in 1996, brings together a set of essays that focus upon mobilization structures and strategies, political opportunities, and cultural framing and ideologies. The essays are comparative and include studies of the former Soviet Union and eastern Europe, the United States, Italy, the Netherlands, and Germany. Their authors are amongst the leaders in the development of social movement theory and the empirical study of social movements